Trajectories of Cognitive Complaints in Patients With Breast Cancer and Their Association With Psychosocial and Neurobiological Factors - Rob Colaes; Gwen Schroyen; Rebeca Alejandra Gavrila Laic; Jeroen Blommaert; Sigrid Hatse; Ann Smeets; Stefan Sunaert; Sabine Deprez (Cancer Medicine)
ABSTRACT Introduction Cancer‐related cognitive impairment (CRCI) is common among patients with breast cancer, with significant variability in both severity and duration of cognitive complaints. This study aimed to elucidate this variability by identifying distinct trajectories of cognitive complaints over time in patients with breast cancer. Additionally, we explored the relationships between these trajectories and various clinical, demographic, psychosocial, neuropsychological, neuroimaging (resting‐state functional MRI, rs‐fMRI), and serum markers. Methods In this prospective study, 67 patients with non‐metastatic breast cancer underwent psychosocial questionnaires, neuropsychological testing, rs‐fMRI, and serum markers at diagnosis (T0), 8 months after diagnosis (T1), and 16 months after diagnosis (T2). Using the partition around medoids (PAM) algorithm on the difference scores of cognitive complaints, patients were clustered into distinct groups. Differences between the groups were assessed using linear mixed effects models. Rs‐fMRI was analyzed using whole‐brain graph theory and connectivity in four cognition‐related networks. Results Four different trajectories of cognitive complaints were identified: stable with no changes in complaints (n = 24), improving with a decrease in complaints at T1 (n = 15), a short‐term affected with an increase in complaints at T1 and recovery at T2 (n = 13), and a long‐term affected with an increase in complaints at T1 and T2 (n = 15). While the groups strongly correlated with changes in the psychosocial measures, only subtle associations were found with neuropsychological tests, serum markers, or rs‐fMRI analyses. Conclusions This research affirmed the presence of distinct trajectories of cognitive complaints in patients with breast cancer, which were associated with differences in anxiety, fatigue, stress, and depression.